Nanomaterial-immobilized lipases for sustainable recovery of biodiesel – A review. (15th May 2022) - Tan, Zhongbiao; Bilal, Muhammad; Li, Xiangqian; Ju, Fang; Teng, Yun; Iqbal, Hafiz M.N.
Highlights: Recent advances in biodiesel recovery using nanomaterial-immobilized lipases. Applications of nanomaterials for enhanced generation of sustainable biodiesel. Contributing factors are discussed for nanomaterials-assisted biofuel production. Abstract: In recent years, the development and deployment of nano-immobilized lipases, as robust biocatalysts, has appeared a promising alternative for biodiesel production. There is a significant hike in using nano-sized support matrices for enzyme-based biotransformation bioprocesses with ever-increasing scientific awareness and nanotechnological advancement. Several nano-scale materials include magnetic and non-magnetic nano-particles, silica nano-particles, carbon nanotubes, graphene/graphene oxide, electrospun nanofibers, metal–organic frameworks, and other nanohybrid matrices are of supreme interest that can shield the catalytic attributes of enzymes after immobilization. Furthermore, nano-sized support matrices immobilized enzymes also offer numerous advantages that native enzymes fail to display on their own, such as high catalytic efficacy, high catalytic turnover, induced stability under harsh reaction conditions, high resistivity against reaction by-products (which otherwise can hinder/inhibit the pristine enzyme), low mass transfer limitation, and high yield under mild processing environment. Lipases are considered principal candidates (biocatalysts) for biodiesel production via transesterification processes, among several industrially relevant enzymes. The nano-immobilized lipases showed a broader working range under different pH and temperature conditions, a highly requisite challenge in indusial settings. Herein, we reviewed several perspectives of sustainable biodiesel production using nano-immobilized lipases. First, following a brief introduction, this review is spotlighting numerous existing and state-of-the-art strategies for lipase immobilization on nanomaterials. Second, the critical factors that characterize nano-biocatalysts are discussed to show the need for optimal reaction conditions to further sustainable transformation. Third, promising nano-carriers to develop lipase-based nanobiocatalyst are given with suitable examples. Fourth, some influential factors that improve the overall performance of nano-immobilized lipases are discussed in terms of the sustainability and processability of the entire production process. Lastly, the contemporary challenges and key considerations for sustained biodiesel production from waste resources are also given for future studies.